PEMBELAJARAN COOPERATIVE LEARNING TIPE NHT PADA SISWA KELAS X MIPA 1 SMA NEGERI 3 PEMALANG - RISTONO RISTONO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to improve the learning outcomes of students of class X MIPA 1 SMA Negeri 3 Pemalang totaling 36 students by using the Cooperative Learning learning model type NHT (Numbered Head Together). This classroom action research is designed in 2 cycles. Each cycle is carried out in 4 stages, namely planning, implementation, observation and reflection. The competency standards in the learning improvement plan for cycle 1 and cycle 2 are analyzing the relationship between ecosystem components, changes in material and energy, and the role of humans in the balance of the ecosystem. The indicators are drawn in the form of diagrams of food chains and food webs of life based on observations of an ecosystem. Then the subject of this research in cycle 1 in the school environment and cycle 2 in an environment not far from the school, namely the rice field ecosystem. The results of classroom action research show that the use of cooperative learning model type NHT (Numbered Head Together) can improve student learning outcomes in class X Mathematics and Natural Sciences 1 for the academic year 2021/2022, with an average student learning outcome of cycle 1 who completes 28 students (75% ), while in cycle 2 which was completed as many as 35 students (97%). The average student learning outcomes increased from 68 in cycle 1, after cycle 2 it increased to 85. Based on the research results obtained, teachers in learning biology always provide learning motivation to students, using teaching aids or media, creating effective learning, using a fun learning model, so they can be active. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar siswa kelas X MIPA 1 SMA Negeri 3 Pemalang yang berjumlah 36 siswa dengan menggunakan model pembelajaran Cooperative Learning tipe NHT (Numbered Head Together). Penelitian tindakan kelas ini dirancang dalam 2 siklus. Setiap siklus dilaksanakan dalam 4 tahap, yaitu perencanaan, pelaksanaan, observasi dan refleksi. Adapun standar kompetensi pada rencana perbaikan pembelajaran siklus 1 maupun siklus 2 yaitu menganalisis hubungan antara komponen-komponen ekosistem, perubahan materi dan energi, serta peranan manusia dalam keseimbangan ekosistem. Indikatornya menggambar dalam bentuk diagram rantai makanan dan jaring-jaring makanan kehidupan berdasarkan hasil pengamatan suatu ekosistem. Kemudian subjek penelitian ini pada siklus 1 di lingkungan sekolah dan siklus 2 di lingkungan yang tidak jauh dari sekolah yaitu ekosistem sawah. Hasil penelitian Tindakan kelas menunjukkan bahwa penggunaan pembelajaran model Cooperative Learning tipe NHT (Numbered Head Together) dapat meningkatkan hasil belajar siswa kelas X MIPA 1 tahun pelajaran 2021/2022, dengan rata-rata hasil belajar siswa siklus 1 yang tuntas sebanyak 28 siswa (75%), sedangkan pada siklus 2 yang tuntas sebanyak 35 siswa (97%). Rata-rata hasil belajar siswa meningkat yang sebelumnya 68 pada siklus 1, setelah siklus 2 meningkat menjadi 85. Berdasarkan hasil penelitian yang diperoleh, guru dalam pembelajaran biologi selalu memberikan motivasi belajar kepada siswa, menggunakan alat peraga atau media, menciptakan pembelajaran yang efektif, menggunakan model pembelajaran yang menyenangkan, sehingga dapat aktif.